Alternatif Protein Pakan Ikan Lele (Clarias sp.) dengan Penambahan Tepung Cacing Sutera (Tubifex sp.) - Arnando, Edo; Ellya, Ellya; Ariani, Indah; Soleh, Muhammad; Susanto, Toni; Hodifa, Veronita; Amin, Mohammad (Seminar Nasional Lahan Suboptimal, 2021)
Arnando E, Ellya E, Ariani I, Soleh M, Susanto T, Hodifa V, Amin M.  2021. Alternative protein feed for catfish (Clarias sp.) with the addition of silkworm flour (Tubifex sp.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 524-533.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Catfish (Clarias sp.) is a fish commodity that has been developed because it has high economic value. The high production value causes demdan to increase, especially maintenance dan feeding with high protein content. Silkworm flour (Tubifex sp.) is a addition of silk worms (Tubifex sp.) as a combination of artificial feed especially to increase the high protein content to support the growth dan development of catfish (Clarias sp.). They studied aimed made deaded silkworms (Tubifex sp.) was reprocessed into fed by made silkworm floured so that the floured could was used as a protein substituted dan could was formulated in othered fed ingredients. The resulted of the studied explained the nutritional contented of silk wormed (Tubifex sp.) in which 57% protein, 13% fat, 4.86% carbohydrates, dan 9.76% water contented. In addition had several important nutritional contented, silk wormed have also been equipped with 13 kinds of amino acids, namely 7 essential amino acids dan 6 non-essential amino acids. So that silk worms (Tubifex sp.) can have a fairly high nutritional content when the nutritional contented was needed by fish seeded for the growth process of catfish. Therefore, the addition of silk worms in feed can stimulate fish to eat which has a high protein content so that it is easily digested dan absorbed to provide optimal utilization of protein intake in terms of growth dan is expected to increase protein in catfish.